2019
DOI: 10.4236/ae.2019.71002
|View full text |Cite
|
Sign up to set email alerts
|

Some Natural Plant Extracts Having Biocide Activities against the American Bollworm <i>Helicoverpa armigera</i> (Lepidoptera: Noctuidae)

Abstract: In the present research, the toxicity, antifeedant activity and biological effects of ethanolic leaves extract of four medicinal plants named Eucalyptus rostrata, Dodonea viscosa, Rhyza stricta and Cymbopogon schoenanthus were evaluated on 2 nd , 3 rd and 4 th instar larvae of H. armigera under laboratory condition. The results showed that values of LC 50 in mg of different plant extracts in mg/100ml of the larval diet can be arranged in an ascending order as follows: Dodonea 7.23 > Cymbopogon 12.59 > Rhazya 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Treatments included with different concentrations of extract to compare with untreated found that there were poor hatching and poor egg-laying. Also, Sharaby et al (2019) evaluated the toxicity, antifeedant activity and biological effects of ethanolic leaves extract of Eucalyptus on H. armigera larvae. All leave extracts cause mortality to larvae and can be used in combination with other methods in the integrated management program.…”
Section: Fig (3) Tem Images Of Agnps (Ab) and The Corresponding DImentioning
confidence: 99%
“…Treatments included with different concentrations of extract to compare with untreated found that there were poor hatching and poor egg-laying. Also, Sharaby et al (2019) evaluated the toxicity, antifeedant activity and biological effects of ethanolic leaves extract of Eucalyptus on H. armigera larvae. All leave extracts cause mortality to larvae and can be used in combination with other methods in the integrated management program.…”
Section: Fig (3) Tem Images Of Agnps (Ab) and The Corresponding DImentioning
confidence: 99%